Unique osteological evidence for human-animal gladiatorial combat in Roman Britain - T. J. U. Thompson; D. Errickson; Christine McDonnell; Malin Holst; Anwen Caffell; John Pearce; Rebecca L. Gowland (PLoS ONE, 2025)
The spectacle of Roman gladiatorial combat captures the public imagination and elicits significant scholarly interest. Skeletal evidence associated with gladiatorial combat is rare, with most evidence deriving from written or visual sources. A single skeleton from a Roman cemetery outside of York where gladiators arguably were buried presented with unusual lesions. Investigation, including comparative work from modern zoological institutions, has demonstrated that these marks originate from large cat scavenging. Thus, we present the first physical evidence for human-animal gladiatorial combat from the Roman period seen anywhere in Europe.